New data on Palaearctic Xantholinini. 9°. Three new Mediterranean species of Xantholinus (Coleoptera: Staphylinidae) [258th contribution to the knowledge of the Staphylinidae] - Bordoni, Arnaldo (Fragmenta entomologica, 2016)
Xantholinus syriacus sp. n., X. tronqueti sp. n. from Syria and X. apterus sp. n. from Algeria are described and figured.